2022
DOI: 10.1111/jopy.12761
|View full text |Cite
|
Sign up to set email alerts
|

Pathways of personality and learning risk for addictive behaviors: A systematic review of mediational research on the acquired preparedness model

Abstract: Objective The Acquired Preparedness (AP) model proposes that impulsive personality traits predispose some individuals to learn certain behavior‐outcome associations (expectancies), and that these expectancies in turn influence the escalation of risky behaviors. This theory has been applied to the development of behaviors such as drinking, drug use, gambling, and disordered eating. In the current study, we aimed to summarize empirical tests of this model over the 20 years since it was proposed. Method We used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 126 publications
(137 reference statements)
1
8
0
Order By: Relevance
“…Consistent with this theory, studies indicate that youth with more positive eating expectancies evidence greater increases in bingeeating symptoms over time (Halvorson et al, 2022;Smith et al, 2007) and EMA studies indicate that momentary increases in eating expectancies contribute to immediate risk for experiencing binge-eating episodes among individuals with binge-eating pathology (Pearson et al, 2018;.…”
Section: Eating Expectanciesmentioning
confidence: 82%
See 1 more Smart Citation
“…Consistent with this theory, studies indicate that youth with more positive eating expectancies evidence greater increases in bingeeating symptoms over time (Halvorson et al, 2022;Smith et al, 2007) and EMA studies indicate that momentary increases in eating expectancies contribute to immediate risk for experiencing binge-eating episodes among individuals with binge-eating pathology (Pearson et al, 2018;.…”
Section: Eating Expectanciesmentioning
confidence: 82%
“…Within the field of eating disorders, researchers have suggested that past experiences of reward from food may contribute to positive eating expectancies (e.g., eating will lead to reductions in negative affect), which could increase risk for subsequent binge eating (Hohlstein et al, 1998). Consistent with this theory, studies indicate that youth with more positive eating expectancies evidence greater increases in binge‐eating symptoms over time (Halvorson et al, 2022; Smith et al, 2007) and EMA studies indicate that momentary increases in eating expectancies contribute to immediate risk for experiencing binge‐eating episodes among individuals with binge‐eating pathology (Pearson et al, 2018; Schaefer et al, 2021).…”
Section: Reward‐related Processes Implicated In Binge‐eating Pathologymentioning
confidence: 93%
“…Finally, the current study used a measure of lack of conscientiousness that combines typical conceptualizations of lack of planning and lack of perseverance, despite research to suggest that the two may have additive effects on substance use outcomes (e.g., Argyriou et al, 2020; Waddell, Gunn, et al, 2021). In addition, acquired preparedness studies have historically focused on a lack of planning as the impulsive trait that biases the learning process related to alcohol (i.e., stronger positive expectancies; Halvorson et al, 2022). Despite research suggesting that a lack of conscientiousness is the higher‐order trait under which both lack of premeditation and lack of perseverance are nested (Cyders et al, 2014), the current study was unable to disentangle a lack of conscientiousness from these two impulsive traits.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, correlations between both traits and positive expectancies were of the same magnitude (r = 0.34, p < 0.001). Thus, although the APM has historically focused on generalized impulsivity/a lack of conscientiousness (Halvorson et al, 2022;Smith & Anderson, 2001) pectancies (e.g., Lee et al, 2018;Waddell, Sternberg, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation